BiVO4 quadrangular nanoprisms with highly exposed {101} facets for selective photocatalytic oxidation of benzylamine. Issue 37 (19th April 2022) - Lv, Min; Tong, Fengxia; Wang, Zeyan; Liu, Yuanyuan; Wang, Peng; Cheng, Hefeng; Dai, Ying; Zheng, Zhaoke; Huang, Baibiao
Abstract : Q-BiVO4 with highly exposed {101} facets exhibits superior photocatalytic BnNH2 oxidation performance. The single-particle PL tests confirm the efficient charge transfer between Q-BiVO4 and BnNH2 . Abstract : Photocatalytic oxidation of amines to high value-added imines is crucial but challenging. The adsorption ability to reactant molecules and the charge separation ability are important factors affecting the reactivity. Different facets of monoclinic BiVO4 (m-BiVO4 ) have varied electronic structures, leading to differences in the adsorption ability and charge separation ability. Thus, tailoring the exposed facets is a promising strategy to optimize the reactivity. Herein, the density functional theory (DFT) calculations demonstrate that for m-BiVO4, both the benzylamine (BnNH2 ) adsorption ability and charge separation ability of {101} facets were stronger than those of {110} facets. These results motivate us to synthesize m-BiVO4 quadrangular nanoprisms (Q-BiVO4 ) with highly exposed {101} facets through a colloidal two-phase method. Q-BiVO4 exhibits highly enhanced charge separation efficiency and excellent photocatalytic performance for oxidizing BnNH2 to N -benzylidenebenzylamine ( N -BB). More impressively, the efficient charge transfer between Q-BiVO4 and BnNH2 was directly confirmed via single-particle spectroscopy in situ . This work provides direct evidence to deeply understand the interaction between Q-BiVO4 and the reactant molecules and provides insights for rational design of photocatalysts with specific exposed facets for selective oxidation of amines.